2020
DOI: 10.1371/journal.pone.0237338
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of patient safety culture among community pharmacists in Ethiopia: A cross-sectional study

Abstract: The study was aimed to explore patient safety culture of community pharmacists working in Dessie and Gondar towns, Northern Ethiopia. Methods A cross-sectional study was conducted from 1 st to 31 st March 2018. In this cross-sectional survey, the Pharmacy Survey on Patient Safety Culture (PSOPSC), developed by the Agency for Healthcare Research and Quality (AHRQ), was used to collect data. PSOPSC is a self-administered questionnaire. The questionnaire was distributed among staffs who work in community pharmaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 24 publications
2
20
0
1
Order By: Relevance
“…The section that deals with descriptive cross-sectional quantitative studies have sections that assess the relevance of the sampling to the research question, the representative of the sample to the target population, appropriateness of the measurements, the risk of nonresponse is low, and whether the statistical method adopted responded appropriately to the research question. All the studies identified in this category had all the responses being affirmative to each type except three [14,[16][17][18][19][20][21][22][23][24][25][26]. The three studies failed to meet the criteria requiring the study sample to represent the population [17,19,26].…”
Section: Quality Appraisalmentioning
confidence: 99%
See 2 more Smart Citations
“…The section that deals with descriptive cross-sectional quantitative studies have sections that assess the relevance of the sampling to the research question, the representative of the sample to the target population, appropriateness of the measurements, the risk of nonresponse is low, and whether the statistical method adopted responded appropriately to the research question. All the studies identified in this category had all the responses being affirmative to each type except three [14,[16][17][18][19][20][21][22][23][24][25][26]. The three studies failed to meet the criteria requiring the study sample to represent the population [17,19,26].…”
Section: Quality Appraisalmentioning
confidence: 99%
“…All the studies identified in this category had all the responses being affirmative to each type except three [14,[16][17][18][19][20][21][22][23][24][25][26]. The three studies failed to meet the criteria requiring the study sample to represent the population [17,19,26]. It was noted that two studies [27,28] evaluated qualitative studies.…”
Section: Quality Appraisalmentioning
confidence: 99%
See 1 more Smart Citation
“…Hal ini disebabkan karena pada saat rekruitmen usia tenaga kefarmasian dibatasi maksimal 35 tahun dan rentang usia tersebut masuk kedalam usia produktif. Penelitian ini sejalan dengan penelitian sebelumnya yang menyebutkan bahwa usia paling produktif berkisar pada usia 19-25 tahun (14) . Responden perempuan lebih besar dibandingkan laki-laki.…”
Section: Hasil Dan Pembahasanunclassified
“…Therefore, community pharmacies have continuously attempted to improve the quality of health and pharmaceutical care services provided to patients, focusing on optimizing patient safety and decreasing unintended mistakes during healthcare delivery. Before the COVID-19 pandemic, several studies assessed patient safety culture in community pharmacy settings both internationally and regionally [ 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Previous research has identified organizational breakdown, insufficient staffing, increased production pressures, and provider fatigue as factors contributing to poor patient safety [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%